A Journey to “Partial Cosmopolitanism” in Michael Ondaatje’s Anil’s Ghost - Valkeakari, Tuire (Studies in Canadian Literature, 2013)
Michael Ondaatje's Anil's Ghost (2000) can be read as a complex, open-ended narrative about cosmopolitanism and its viability as a moral choice and way of life. While Ondaatje's portrait of his protagonist, Anil -- a transnational nomad whom many scholars consider privileged, indifferent, and detached -- has evoked conflicting critical responses, Kwame Anthony Appiah's concept of "partial cosmopolitanism" offers a fitting interpretive key to understanding her role in the novel. Appiah, accepting neither strict cosmopolitanism nor anti-cosmopolitanism, promotes a version of cosmopolitanism that both recognizes the existence of a global human community that creates universal moral obligations and argues that we have special responsibilities to those closest to us, including our compatriots (hence the attribute "partial"). As many critics have observed, Anil's Ghost acknowledges at the outset the cosmopolitan Anil's alienation from her country of origin, Sri Lanka. However, the novel also depicts the formation of an emotionally and morally significant reconnection that gradually facilitates the emergence of Anil's "partial cosmopolitanism" in the sense proposed by Appiah. Anil's work assignment in her war-torn native country ends tragically, but it is the war, not the ethics of the partial cosmopolitan, that the narrative condemns.